Jewish identities in the American West : relational perspectives - Eisenberg, Ellen (Brandeis series in American Jewish history, culture, and life., 2022)
"With essays that cover the period from the mid-nineteenth century to the present, this volume presents a collective portrait of change over time that allows us to view the shifting nature of Jewish identity in the U.S. West, as well as the evolving frameworks for racial construction"--